To give the literary event: Blanchot and Lawrence's narratives of life/death. Issue 4 (3rd April 2023) - Tan, Ian
ABSTRACT: This essay explores the poststructuralist concept of the 'event' as an unforeseen and incalculable surprise, reading its theoretical significance in two ways: as an occurrence that has already taken place (divided at its source) and an occurrence that opens up the impossible consideration of futurity. By linking the thought of the event with the phenomenological notion of the gift, I aim to explore how literary narratives perform the happening of the event through the conditions of absolute givenness, undercutting notions of power, possession and mastery in the work of language. Through a reading of Maurice Blanchot's Thomas the Obscure and D.H. Lawrence's The Man Who Died, I demonstrate how narratives articulating themselves at the boundaries of life and death inform theoretical thinking of the event by collapsing the boundaries separating biography and mortality, inducting us into an asynchronous temporality and economy of givenness.